2012
DOI: 10.1097/mbc.0b013e3283513a97
|View full text |Cite
|
Sign up to set email alerts
|

Use of the novel thrombopoietin receptor-agonist romiplostim, in combination with steroids and immunoglobulins for the increase of platelets prior to splenectomy, in refractory immune thrombocytopenia

Abstract: This case report describes a patient with relapsed primary immune thrombocytopenic purpura (ITP), in which splenectomy was not possible due to the persistence of a low platelet count despite treatment with corticosteroids, intravenous immunoglobulins (IVIG) and platelet transfusion treatment. As an attempt to increase platelet count prior to performing splenectomy, the thrombopoietin receptor agonist, romiplostim, was administered in combination with steroids and IVIG. A single administration of romiplostim wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The correction of thrombocytopenia in CLD improves general health by correction of bleeding tendency. This match with many clinical case reports that shown a possible role of Romiplostim in the preparation preliver transplant or prior for invasive therapeutic procedure (Dultz et al, 2011 andSivera et al, 2012). In addition, this improvement in the general health allows and improves effect of other medications used in the treatment of CLD.…”
Section: 2014) Thrombocytopenia Is Frequently Present In the Patients With Cld (Schuppan And Kim 2013)supporting
confidence: 80%
“…The correction of thrombocytopenia in CLD improves general health by correction of bleeding tendency. This match with many clinical case reports that shown a possible role of Romiplostim in the preparation preliver transplant or prior for invasive therapeutic procedure (Dultz et al, 2011 andSivera et al, 2012). In addition, this improvement in the general health allows and improves effect of other medications used in the treatment of CLD.…”
Section: 2014) Thrombocytopenia Is Frequently Present In the Patients With Cld (Schuppan And Kim 2013)supporting
confidence: 80%
“…Baldini et al described a patient with transient thrombocytosis after using romiplostim to augment platelet count prior to splenectomy in a patient with ITP secondary to non-Hodgkin lymphoma [21]. Similarly, Sivera et al reported a case of transient thrombocytosis after romiplostim was used to augment platelet count prior to splenectomy in a patient with ITP refractory to steroids and IVIG and with significant uterine bleeding [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Many recent clinical case reports have shown a possible role of romiplostim in the preparation preliver transplant or prior for invasive therapeutic procedure .…”
Section: Discussionmentioning
confidence: 99%